Ribosome distribution in HeLa cells during the cell cycle. - Yuan-Jhih Tsai; Hsing-I Lee; Alan Lin (PLoS ONE, 2012)
In this study, we employed a surface-specific antibody against the large ribosome subunit to investigate the distribution of ribosomes in cells during the cell cycle. The antibody, anti-L7n, was raised against an expansion segment (ES) peptide from the large subunit ribosomal protein L7, and its ribosome-surface specificity was evident from the positive immuno-reactivity of ribosome particles and the detection of 60 S immune-complex formation by an immuno-electron microscopy. Using immunofluorescent staining, we have microscopically revealed that ribosomes are dispersed in the cytoplasm of cells throughout all phases of the cell cycle, except at the G2 phase where ribosomes show a tendency to gather toward the nuclear envelope. The finding in G2 cells was confirmed by electron microscopy using a morphometric assay and paired t test. Furthermore, further observations have shown that ribosomes are not distributed immune-fluorescently with nuclear envelope markers including the nuclear pore complex, the integral membrane protein gp210, the inner membrane protein lamin B2, and the endoplasm reticulum membrane during cell division we propose that the mechanism associated with ribosome segregation into daughter cells could be independent of the processes of disassembly and reassembly of the nuclear envelope.